Simulation of Motorcycle Smart Handling With Addition Gyroscopic Component - I.K.A. Atmika; I.N. Sutantra; Agus S. Pramono (IPTEK The Journal for Technology and Science, 2009)
Motorcycle in its operation needs high stability. To improve a stability of motorcycle especially in turning direction is done by many methods. The handling turn inclination angle of motorcycle with addition gyroscopic component will be discussed in this research. Gyroscopic is systems which have function to against from Centrifugal (Fc) force. The aim of using Gyroscopic is to control and handling turn inclination angle to avoid skidding.This research uses of simulation model with input of design and dynamic parameter. Speed variable to be used are 40, 50, 60, 70, 80, 90, 100 km/hour. The simulation is processed by Matlab 7.0.1. The result of research is concluded as : the Gyroscopic has controlled skid performance and inclination angle of motorcycle about 11%.